Limiting Damage to 2D Materials during Focused Ion Beam Processing. Issue 12 (13th August 2020) - Andersen, Anton Bay; Shivayogimath, Abhay; Booth, Tim; Kadkhodazadeh, Shima; Hansen, Thomas Willum
Abstract : 2D materials are by definition just a few atomic layers thick. They are therefore ideal samples for transmission electron microscopy, in the plan‐view geometry. However, 2D materials are typically placed or grown on substrates, which in some cases requires analysis to be performed on cross sections. In this case focused ion beam preparation is often the technique of choice for producing thin lamellae, but damage to the surface of 2D material during imaging and milling must be mitigated. Herein, it is demonstrated that the typically applied electron beam‐assisted deposition of platinum and carbon prior to milling does not provide sufficient protection, and results in significant damage. Instead, it is found that arc‐evaporated carbon—deposited with a standard carbon coater designed for scanning electron microscopy (SEM) samples—can provide sufficient protection, enabling cross‐sectional analysis without detectable damage to monolayer or bilayer samples subsequently prepared by standard focused ion beam preparation procedures. Abstract : Preparing exposed 2D material surfaces for atomic level cross‐sectional investigations requires surface damage to be minimized. This work presents a simple procedure for eliminating the surface damage, measurable with transmission electron microscopy, scanning transmission electron microscopy, and electron energy‐loss spectroscopy, during focused ion beam preparation of lamella of exposed MoS2 on gold using evaporated carbon.